Electrochemical oxidation of iron and alkalinity generation for efficient sulfide control in sewers. (1st July 2017) - Lin, Hui-Wen; Kustermans, Caroline; Vaiopoulou, Eleni; Prévoteau, Antonin; Rabaey, Korneel; Yuan, Zhiguo; Pikaar, Ilje
Abstract: The addition of iron salts is one of the most commonly used dosing strategies for sulfide control in sewers. However, iron salts decrease the sewage pH which not only reduces the effectiveness of sulfide precipitation but also enhances the release of residual sulfide to the sewer atmosphere. Equally important, concentrated iron salt solutions are corrosive and their frequent transport, handling, and on-site storage often come with Occupational Health and Safety (OH&S) concerns. Here, we experimentally demonstrated a novel sulfide control approach using electrochemical systems with parallel placed iron electrodes. This enabled combining anodic dissolved iron species release with cathodic hydroxyl anion production, which alleviates all the aforementioned concerns. A long-term experiment was successfully carried out achieving an average sulfide removal efficiency of 95.4 ± 4.4% at low voltage input of 2.90 ± 0.54 V over the course of 8 weeks. This electrochemical method was demonstrated to successfully achieve efficient sulfide control. In addition, it increases the sewage pH, thereby overcoming the drawbacks associated with the pH decrease in the case of conventional iron salt dosing. Ferrous ions were produced at an overall coulombic efficiency (CE) of 98.2 ± 1.2%, whereas oxygen evolution and direct sulfide oxidation were not observed. Short-term experiments showed that increasing either inter-electrode gap or current density increased the cell voltage associated with the increase in the ohmic drop of the system. Overall, this study highlights the practical potential of in-situ generation of dissolved iron species and simultaneous hydroxyl anion generation for efficient sulfide control in sewers. Graphical abstract: Highlights: Dissolved iron species generated electrochemically in sewage for sulfide control. Sulfide removal efficiency of 95.4 ± 4.4% achieved in long-term experiments. Sewage pH increased by concomitant OH − generation.